2019
DOI: 10.1080/03019233.2019.1672447
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental investigation of solidification structure evolution and reduction of centre segregation in continuously cast GCr15 bloom

Abstract: A CAFE model and SDAS model are established in order to study evolutionary behaviour of macrostructure and secondary dendrites on 220 × 260 mm 2 bloom cross-section of GCr15 bearing steel, respectively. Based on numerical simulation and experiments, the effects of process parameters on centre ECR and SDAS are investigated. It is found that increase of centre ECR and decrease of SDAS occur with the decrease of superheat and with the increase of M-EMS. The results reveal that M-EMS and superheat exhibit a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Zhao et al [10] adopted a two-dimensional cellular automaton (CA) model and finite element (FE) method to simulate solidification structure formation during continuous casting of beam billet, which represents the growth of columnar and equiaxial dendrites under detailed secondary cooling boundary conditions. An et al [11] established the CAFE model and SDAS model in order to study the evolutionary behavior of macrostructure and secondary dendrites, respectively, on a 220 × 260 mm 2 bloom cross-section of GCr15 bearing steel. Based on numerical simulation and experiments, the effects of process parameters on center ECR and SDAS are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [10] adopted a two-dimensional cellular automaton (CA) model and finite element (FE) method to simulate solidification structure formation during continuous casting of beam billet, which represents the growth of columnar and equiaxial dendrites under detailed secondary cooling boundary conditions. An et al [11] established the CAFE model and SDAS model in order to study the evolutionary behavior of macrostructure and secondary dendrites, respectively, on a 220 × 260 mm 2 bloom cross-section of GCr15 bearing steel. Based on numerical simulation and experiments, the effects of process parameters on center ECR and SDAS are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The formation mechanisms of center segregation have been investigated by many researchers. [3][4][5][6][7] The low superheat casting, [8][9][10] electromagnetic stirring, [11][12][13][14] and mechanical reduction [15][16][17][18] were proposed to reduce the center segregation defect in the continuous casting. However, the influence of RGD [19,20] on solute redistribution is less studied, even though it is commonly observed in the continuous caster.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the segregation defect in continuous casting, several methods have been proposed. As to lower superheat casting, An et al [ 8 ] indicated that the equiaxed zone ratio increased, the columnar zone reduced, and the secondary arm spacing decreased. With the superheat lower than 10 °C, Pikkarainen et al [ 9 ] reported that the center negative segregation formed, due to the globular grain sedimentation.…”
Section: Introductionmentioning
confidence: 99%
“…El-Bealy et al [7] established mathematical models to predict SDAS, and found that SDAS has an exponential relationship with the local solidification time (LST). An et al [8] found smaller SDAS can make the solidification…”
mentioning
confidence: 99%